2014
DOI: 10.14202/vetworld.2014.635-638
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tetracycline resistance determinant tetA gene and antimicrobial resistance pattern in Escherichia coli isolates recovered from healthy layer chickens

Abstract: Aim:The aim was to study the occurrence of tetracycline resistance determinant tetA gene, and antibacterial resistance pattern in commensal Escherichia coli recovered from healthy non-clinical layer chickens. Materials and Methods:Twenty-four cloacal swabs were obtained from 15 flocks in five different layer farms located at around Namakkal, which is a place of high-intensity layer chicken rearing in south India. Identification of E. coli was carried out by performing cultural and biochemical tests. Antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Neupane et al (2005) reported no resistance against Amikacin in poultry isolates and 90% sensitive showed by Bist et al (2014). Result of sensitivity of Amikacin of this study is contrast to study of Priti and Satish (2014) and Balasubramaniam (2014) in which resistance of Amikacin was 88.33% and 71% respectively. Resistance against Amikacin was observed 10.68% in this study.…”
Section: Resistancecontrasting
confidence: 78%
See 1 more Smart Citation
“…Neupane et al (2005) reported no resistance against Amikacin in poultry isolates and 90% sensitive showed by Bist et al (2014). Result of sensitivity of Amikacin of this study is contrast to study of Priti and Satish (2014) and Balasubramaniam (2014) in which resistance of Amikacin was 88.33% and 71% respectively. Resistance against Amikacin was observed 10.68% in this study.…”
Section: Resistancecontrasting
confidence: 78%
“…of Co-trimoxazole (sulphamethoxazole+trimethoprim) was found 86.40% and got similarities of finding of Balasubramaniam et al, (2014) 83%, Salehi and Bonab (2006) 80% and Bukhrosh and Hamdi (2013) 82.2 %. Haghighi and Peighambari (2005) also reported 94% resistance in COT which is also similar to this study.…”
Section: Resistancementioning
confidence: 51%
“…AMR reduces the effectiveness of antibiotic treatment and thus leads to increased morbidity, mortality, and healthcare expenditures [8]. Commensal E. coli found in people and animals is considered a potential reservoir for AMR genes [9] and these genetic traits can be transferred to E. coli or to other bacteria found in people, animals, and in the environment [10]. Presumably, water sources contaminated with AMR bacteria is one contributing factor for the higher prevalence of antibiotic resistant bacteria from people living in low-income countries [11].…”
Section: Introductionmentioning
confidence: 99%
“…Frequencies of tet(A) and tet(B) among E. coli isolates were 66% and 42%, respectively. A study conducted on E. coli isolated from healthy layer flocks in India showed that 88% of isolates were resistant to tetracycline and tet(A) was found in 29% of isolates (Balasubramaniam et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the presence of the tetracycline resistance genes tet(A) and tet(B) in tetracyclineresistant E. coli isolated from broiler and layer chickens (Zhang et al, 2012;Balasubramaniam et al, 2014). In Iran, poultry meat is the most widely produced and consumed meat protein source.…”
Section: Introductionmentioning
confidence: 99%